Black solo garlic protects hepatic and renal cell function in streptozotocin-induced rats - Saryono,; Sarmoko,; Nani, Desiyani; Proverawati, Atikah; Taufik, Agis (Frontiers in Nutrition, 2022)
Black solo garlic has been evaluated for its ability to reduce free radicals, however, the safety test on kidney and liver function have not been evaluated. This study aimed to examine the effect of brewed black solo garlic on liver (total protein, albumin, glutathione S-transferase/GST) and kidney (urea, creatinine, -2-microglobulin) functions in streptozotocin (STZ)-induced white rats. The experimental animals were randomly divided into six groups, each including five animals. The groups consist of the normal control group, STZ-induced control group, the black solo garlic treatment group with doses 6.5, 13.5 and 26 g/kg body weight, and metformin positive control. After STZ induction, the serum levels of GST, total protein, and albumin decreased. After treatment with black solo garlic, the serum level of GST, total protein, and albumin increased significantly (p<0.05). The levels of urea, creatinine, and β2-microglobulin increased after STZ induction. After treatment of black solo garlic, levels of urea, creatinine, and β2-microglobulin decreased significantly (p<0.05). These results suggest that black solo garlic use is safe for the liver and kidneys of STZ-induced rats.